The study protocol for a pseudo-randomised pre-post designed controlled intervention trial to study the effects of a 7-week cooking program on self-efficacy and biomarkers of health: the ECU lifestyle and biomarkers get connected study (ECULABJMOF) including the Jamie's Ministry of Food WA participant experience - Joanna Rees; Claus C. Christophersen; Joshua R. Lewis; Johnny Lo; Ros Sambell; Leesa Costello; Cailyn Walker; Matt F. Byrne; Mary C. Boyce; Robert U. Newton; Amanda Devine (BMC, 2020)
Abstract Background Australia, like other nations, has experienced a shift in dietary patterns away from home cooking of nutritious foods, towards a reliance on pre-prepared convenience meals. These are typically energy-dense, nutrient-poor and contribute to the rising prevalence of obesity and chronic disease burden. The aims of this study were to evaluate whether a community-based cooking program instigated a change to participants' skills, attitudes, knowledge, enjoyment and satisfaction of cooking and cooking confidence (self-efficacy). Methods The pseudo-random, pre-post study design consisted of an intervention and a control group. Participant recruitment and group allocation was based on their program start dates. Intervention participants were surveyed three times (baseline, 7 weeks and 6 months) and the control group were surveyed at baseline and 5 weeks. All participants were registered via an online website and were 18 years or over. Upon consent, participants were offered four levels of commitment, defined by different assessments. The minimum participation level included an online survey and levels 2, 3 and 4 involved attendance at a clinic with increasing functional, anthropometric and biomarker measurements. Primary endpoints were participants' cooking confidence as a proxy for self-efficacy. Secondary endpoints were dietary intake, physical activity levels, body composition, anthropometry, blood, urine and faecal biomarkers of systemic, physical and mental health. Discussion The community cooking program provided participants with information and advice on food sourcing, preparation and nutrition to improve home cooking skills. The study was designed to explore whether food literacy programs are efficacious in improving participant physical health and well-being in order to combat the rise in obesity and diet-related disease. It will support future use of public health cooking program initiatives aimed at improving food literacy, self-efficacy and physical and mental health. The extensive data collected will inform future research into the relationship between diet, the gut-microbiota and human health. Trial registration Retrospectively registered on 16.08.2019 with the Australian New Zealand Clinical Trials Registry (ANZCTR). ACTRN12619001144101 . Protocol version 4.